The health aspects of skiing - Kubas, Maria; Krzemińska, Katarzyna; Czerwik, Julia; Kuszneruk, Julia; Kłusek, Magdalena; Chawrylak, Katarzyna; Kubas, Wojciech; Sadok, Aleksandra (Quality in Sport, 2024)
Introduction and Purpose: This article presents a comprehensive analysis of the risks and benefits associated with downhill skiing. The article elucidates the prevalence and etiology of common injuries, while also delineating the salutary effects of engaging in the sport. Methods: A literature search was conducted using PubMed and Google Scholar, focusing on articles from 2019 to 2024, including observational studies, clinical trials, meta-analyses and systematic reviews. State of Knowledge: Skiing is a globally popular winter sport, attracting millions of enthusiasts each year. The sport’s combination of outdoor adventure, social activity, and the allure of winter landscapes contribute to its enduring global popularity. Despite its global popularity, skiing carries a significant risk of injury, with knee injuries, particularly ACL sprains, being the most common, especially among women. Despite these risks, alpine skiing offers significant physical health benefits, including improved cardiorespiratory fitness, muscle strength and mental health, making it a beneficial lifelong sport, particularly for older adults. Conclusion: It is notable that while injuries such as ACL sprains and fractures are prevalent, particularly among beginners and those who engage in risk-taking activities, the sport also offers significant health benefits. Alpine skiing has been demonstrated to enhance cardiorespiratory fitness, muscle strength, and mental well-being, thereby conferring significant benefits that extend throughout the lifespan, despite the potential for injury.